WORKSHOP ON TOEFL ITP FOR STUDENTS AT VOCATIONAL SECONDARY SCHOOL NAHDLATUL ULAMA BANTARAN PROBOLINGGO - Hamdani, Beny; Zainuddin, Zainuddin (Faculty of Letters Universitas Abdurachman Saleh Situbondo, 2024)
The TOEFL ITP, or English Language competency Test, is an international language assessment tool used to gauge a speaker's English language competency if it is not their mother tongue. The goal of the TOEFL ITP workshop was to increase the students' understanding of international Standard English language tests among those attending Nahdlatul Ulama Vocational High School in Bantaran Probolinggo. Students from the Nahdlatul Ulama Vocational High School on the banks of Probolinggo who participated in extracurricular English activities made up the workshop participants. The target audience was chosen with the knowledge that students' TOEFL ITP abilities were lacking. Thirty students who participated in the extracurricular English program came to this event. The approach taken for this community service project is a two-month workshop and help with different English language questions from the TOEFL ITP exam, which includes the hearing part, written expression, structure, and reading comprehension. Many students improved their scores from before to after this program and demonstrated mastery of the material covered in the international standardized English test. The Nahdhatul Ulama Bantaran Probolinggo vocational high school students who were getting ready to enter the workforce were greatly impacted by this exercise.